PENINGKATAN HASIL BELAJAR MELALUI MODEL PROBLEM BASED LEARNING TERINTERGRASI BRAINSTORMING BERBASIS MODUL - Darmawan Harefa; Kalvintinus Ndruru; Efrata Gee; Mastawati Ndruru; Lies Dian Marsa Ndraha; Murnihati Sarumaha (HISTOGRAM: Jurnal Pendidikan Matematika, 2020)
The results study indicate that the learning process in class VII-A semester 2 of SMP Negeri 2 Fanayama is increasing. This increase was seen in the processing observation sheets student the activities through the process of cycle I, namely the average percentage of observations student the activity 71,39% and the percentage experiencing an increase in cycle II, which was 76,6%. 77,43% experienced an increase in the process through the second cycle obtained by an average of 82,82% which explained that learning outcomes students class VII-A semester II of SMP Negeri 2 Fanayama 2018/2019 Academic Year the discussion lines and angles there was an increase. This increase is seen the processing the results of learning test process through the first cycle obtained an average percentage success 73,82% and the percentage of incompleteness of 26,18%; processing results the second cycle learning process test obtained average with success percentage of 75,87% and with percentage of incompleteness of 24,13% thus results learning process of have reached the graduation target.